Association of Life's Simple 7 with mild cognitive impairment in community-dwelling older adults in China: a cross-sectional study - Yang, Mengshu; Liu, Yilan; Hu, Xiuzhen; Ren, Dianxu; Yang, Qing; Mao, Jing; Chen, Jing (Frontiers in Aging Neuroscience, 2023)
Background: The Life’s Simple 7 (LS7), a metric composing of seven intervenable cardiovascular risk factors, is initiated by American Heart Association to improve cardiovascular health. Components of LS7 have been reported as risk factors for dementia. However, few study investigated the association between LS7 metric and mild cognitive impairment (MCI). Methods: The study was carried out in a primary care facility between June 8 to July 10, 2022. A total of 297 community-dwelling residents aged 65 years or older were recruited. Sociodemographic, comorbidity, lifestyle characteristics were collected through the questionnaires, biological parameters were obtained from blood sample examinations. Logistic regression was used to analyse the association between LS7 scores (overall, behavioral and biological) and individual components with MCI, adjusting sex, age, education, and cardiovascular disease (CVD). Results: In comparison with the cognitively intact group (n = 195), the MCI group (n = 102) had lower education level and higher proportion of hypertension. Multivariate logistic regression analysis, adjusting sex, age, education and CVD, demonstrated a significant association between MCI and overall LS7 score (odd ratio = 0.805, 95% confidence interval (0.690, 0.939)) and biological score (odd ratio = 0.762, 95% confidence interval (0.602, 0.965)). Conclusion: LS7 was associated with MCI in community-dwelling older adults, indicating that LS7 could be used as guidance in prevention of dementia in community.